The School of Hadith in Al-Rayy, and Its most prominent Sheikhs in the Fourth and Fifth Centuries Alhijrii (Islamic Sciences Journal, 2023)
The city of Maru is one of the most important cities of Khurasan and the Islamic Mashreq in the era of the intellectual renaissance in the fifth and sixth centuries AH. All that scientific activity has shown large elite of scientists in various sciences, but what concerns us in this research is to shed light on the school of hadith and its most prominant sheikhs who excelled in this honorable science. In this city, some of them lived there until he died, and some of them moved to the rest of the cities of Khurasan or outside it.The city of Maru is so fortunate in studying the noble hadith and its sciences by its most prominent sheikhs, whose interest was focused on the hadith of the Messenger, may God bless him and grant him peace, and because of the nature of the request for hadith in those eras, the scientific journey and travel were among the conditions for the seeker of knowledge to obtain the high chains of transmission.” Al-Basti said: this is from the etiquette of the student of hadith: to begin by listening from the sheikhs of the people of his Egypt from the first, then the first in terms of knowledge, fame, honor and other things, then after taking the journey to the one who was of this quality in his time, even if a drop is far from his drop. Attending knowledge circles at the sheikhs of this science is important for listening or for permission.As Muslims are keen on the second source of legislation in our true religion since the era of the Companions and followers to this day, they have taken care of collecting and transcribing hadith, and standing on every word spoken by our honorable Messenger, and setting the necessary rules for this science.